Corporate Training for Effective Performance
XVIII, 267 p.
Keywords: Corporate training and effective performance have become major issues in the 1980s and '90s. Reviews of the training research literature show that, parallel to the growing attention to corporate training, research has also increased in the field, giving a better understanding of the subject and providing fundamental expertise on which trainers can build. The contributions to the book differ in the degree to which they are related to performance issues, but all chapters underline the necessity of thinking from the perspective of effective performance.